Risk Factors for Breast Cancer: Hormonal Contraception - Yuniastini, Yuniastini; Murhan, Al; Purwati, Purwati; Pratiwi, Mutia Diah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
By the end of 2020, there were 7.8 million living women, who were diagnosed with breast cancer in the last 5 years, and it makes breast cancer as the most common cancer in women in the world. There are many breast cancer risk factors, and hormonal contraception is one of them.  The purpose of this research is to analyze risk factors for breast cancers, which are associated with the duration of contraceptive use. Its benefits are to evaluate the usage of hormonal contraception and to get the data used by the government in order to make health policy in preventing breast cancer. This observational research used case control for its study design. There were 150 women, as samples involved in the research, who were suffering from breast cancers and were registered as patients at Abdul Moeloek General Hospital and Jenderal Ahmad Yani Hospital, and other 150 women who had never been diagnosed with breast cancer.  Data were collected by having a direct and telephone interview. The result showed that the number of breast cancer patients who used hormonal contraception was higher than those who use non-hormonal contraception (ratio 55%: 36%). The number of breast cancer patients who used hormonal contraception for 5 years or more was higher than those who used hormonal contraception for less than 5 years (ratio 63% : 29%). Logistic regression analysis showed that there were no associated impacts on the usage of hormonal contraception (p=0,406). There were associated impacts on the duration of hormonal contraception with breast cancers (p=0,00).In conclusion, hormonal contraceptive use increased the risk of breast cancers, and further discussion and individual riskbenefit analysis were needed to be conducted for hormonal contraception users. Abstrack: Hingga akhir tahun 2020,ada 7,8 juta wanita hidup yang didiagnosis kanker payudara dalam 5 tahun terakhir, sehingga menjadikannya sebagai  kanker paling umumdi dunia. Salah satu faktor resiko kanker payudara adalah kontrasepsi hormonal. Tujuan penelitian ini, menganalisis faktor resiko kanker payudara yang berhubungan dengan penggunaan serta lama penggunaan kontrasepsi hormonal. Manfaat penelitian yakni mengevaluasi penggunaan KB hormonal, serta mendapatkan data yang dapat digunakan pemerintah untuk membuat kebijakan kesehatan dalam pencegahan kanker payudara. Jenis penelitian observasi. Desain case control.  Jumlah sampel sebanyak 150 wanita penderita kanker payudara yang terdaftar di RSAM dan RSAY Metro tahun 2019 serta 150 wanita tidak pernah menderita kanker payudara. Teknik pengumpulan data dokumentasi dan wawancara langsung atau pertelepon. Hasil yang didapat, penderita kanker payudara lebih banyak yang menggunakan kontrasepsi hormonal dibandingkan non hormonal (rasio 55%: 36%). Penderita kanker payudara lebih banyak yang menggunakan kontrasepsi hormonal (lebih dari 5 tahun) dibandingkan (kurang dari 5 tahun) (rasio 63%: 29%). Hasil uji regresi logistik, tidak ada pengaruh penggunaan KB hormonal (p=0,406). Ada pengaruh lama pemakaian KB hormonal terhadap kejadian kanker payudara (p=0,00,).  Kesimpulan, lama penggunaan kontrasepsi hormonal diindikasikan meningkatkan risiko kanker payudara, sehingga untuk pencegahan kanker payudara, perludilakukan diskusi dan analisis risiko-manfaat secara individual bagi pengguna kontrasepsi hormonal.